Digi-Housekeeping: The Invisible Work of Flexibility. (December 2020) - Whiting, Rebecca; Symon, Gillian
From an analysis of everyday practices of flexible working captured in video diaries, a form of pervasive but invisible support work is identified and presented. Labelled 'digi-housekeeping', this is work that is required to maintain the digital tools that enable flexible working, and incorporates the tasks of clearing, sorting, preparing, provisioning and troubleshooting. Through the sociocultural processes of responsibilization, personalization and work extension, interpreted here as emblematic of wider neoliberal contemporary work arrangements, digi-housekeeping is devalued and made invisible, characterizing these tasks as not 'real' work. Classifying these tasks as not 'real' work is a new kind of boundary work that supports the continuing displacement of work activities onto individual workers. It is argued that such tasks need to be made visible in order to address feelings of work intensification.